RENCANA STRATEGIS DINAS PEKERJAAN UMUM KABUPATEN BENGKULU UTARA TAHUN 2016-2021 - Rizky Syafputra; Novliza Eka Patrisia (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
This research is the result of observations and interviews conducted by researchers to find out and analyze the Strategic Plan of North Bengkulu Regency. The formulation of the problem in this study is how the implementation of the Strategic Plan (Renstra) policy at the Public Works and Spatial Planning Office of North Bengkulu Regency 2016-2021 and see what are the inhibiting factors in the policy. The purpose of this research is to see the implementation of the Strategic Plan of the Public Works and Spatial Planning Office of North Bengkulu Regency in 2016-2021. Researchers used descriptive qualitative research methods. In this study the data used were primary and secondary data. Primary data is data taken directly at the Department of Public Works and Spatial Planning North Bengkulu Regency, while secondary data is obtained from other parties through interview techniques, observation, documentation and literature study.The results of this study show that the strategic planning policies at the Public Works and Spatial Planning Office are already running well in accordance with existing regulations, all strategic planning techniques are used to design activities for the next five years. In the target groups, the implementation of the Strategic Plan policy seems to have reached its objectives. The organization for implementing the Strategic Plan still has technical and administrative obstacles. The number of new regulations issued, the reduced funds proposed in the Renstra made the implementation of the Strategic Plan ineffective. There are still community groups that do not support the Renstra activities until the Renstra activities are hampered. thus reducing time efficiency for implementing Renstra activities.